Moral responsibility for character - Lumb, Colin Stewart (Department of Philosophy, 2023)
The aim of my thesis is to fill a gap in virtue ethics. I present an account of moral responsibility that is consistent with the core assumption of virtue ethics, that character and not action is the primary locus of ethical appraisal. Virtue ethics typically does not include a notion of moral responsibility. The reason for this omission is that traditionally attributions of moral responsibility are determined by the causal aetiology of our actions. Because virtue ethics is primarily concerned with our characters and not our actions, virtue ethicists typically assume that causal aetiology is irrelevant to ethics. So, in order to fill the gap in virtue ethics I need to show how the core assumption of virtue ethics does not require virtue ethicists to hold that causal aetiology is irrelevant to ethics. The project of filling this gap in virtue ethics is important because virtue ethics is a popular modern ethical theory and in order to fulfil this ·function it must say something about moral responsibility. It is a deficit of virtue ethics that it provides us with no basis for judgements about moral responsibility. It restricts the scope of ethics to simply grounding moral assessments of our characters. An ethical theory needs to provide a basis for making practical decisions in legal and political matters. My thesis is that by shifting the locus of moral responsibility from the notion of action to that of character, virtue ethics can include a notion of moral responsibility. I present an account of the notion of moral responsibility for character. It operates as an amendment to virtue ethics and is intended to demonstrate how differences in the causal aetiologies of our characters determine the extent to which we can be attributed moral responsibility for them. In contrast to, for example, Classical Utilitarianism ii which holds that being morally responsible is an all-or-nothing affair, my account explains how the differences among the causal aetiologies of our characters create a spectrum along which moral responsibility can be assigned to varying degrees. By focusing on the formation of character and not of action as the basis for attributions of moral responsibility we can make use of the notion of a causal aetiology without being forced to abandon the core assumption of virtue ethics. My method is a standard philosophical method of critical analysis and synthesis of philosophical literature. My account consists of two conditions that are both necessary and together sufficient for making attributions of moral responsibility for character. The first condition, which derives from Harry Frankfurt's theory of moral responsibility, is that we 'identify' with our characters. The second condition, which incorporates Daniel Dennett' s notion of a 'narrative self', is that we are to a significant extent 'morally responsible selves'. My conclusion is that we are morally responsible for our characters only if (1) we are to a significant extent morally responsible selves and (2) we identify with our characters. The extent of the attribution of moral responsibility is determined by the extent to which we identify with our characters.